Psychiatric disturbance, urgency, and bacteriuria in children with day and night wetting. Issue 8 (August 1977) - Berg, I; Fielding, D; Meadow, R
Abstract : Forty children with day and night wetting were compared with 46 with night wetting only to see if day wetting was then associated with particular clinical features. Interviews with mothers, questionnaries completed by teachers, physical investigations, and measurement of functional bladder capacities were used. Day wetting combined with bed wetting occurred equally in boys and girls and was associated with daytime urgency and greater frequency of psychiatric disturbance. In boys, soiling was also associated. In girls, bacteriuria, which appeared to be caused by the day wetting, occurred in about 50%. Neither daytime frequency nor small functional bladder capacity were specifically related to day wetting.